It Hurts to Ask - Roland Benabou; Ania Jaroszewicz; George Loewenstein (Institute of Labor Economics (IZA), 2022)
We analyze the offering, asking, and granting of help or other benefits as a three-stage game with bilateral private information between a person in need of help and a potential help-giver. Asking entails the risk of rejection, which can be painful: since unawareness of the need can no longer be an excuse, a refusal reveals that the person in need, or the relationship, is not valued very much. We show that a failure to ask can occur even when most helpers would help if told about the need, and that even though a greater need makes help both more valuable and more likely to be granted, it can reduce the propensity to ask. When potential helpers concerned about the recipient's ask-shyness can make spontaneous offers, this can be a double-edged sword: offering reveals a more caring type and helps solve the failure-to-ask problem, but not offering reveals a not-socaring one, and this itself deters asking. This discouragement effect can also generate a trap where those in need hope for an offer while willing helpers hope for an ask, resulting in significant inefficiencies.
Keywords: D03; D23; D64; D82; D83; D91; 330; helping; asking; rejection; respect; shyness; altruism; cooperation; prosocial; image; reputation; information aversion